2014
DOI: 10.1128/jcm.02199-14
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption Ionization–Time of Flight (MALDI-TOF) Mass Spectrometry Using the Vitek MS System for Rapid and Accurate Identification of Dermatophytes on Solid Cultures

Abstract: d; POLE Pharma Consulting, Breganzona, Switzerland e The objective of this research was to extend the Vitek MS fungal knowledge base version 2.0.0 to allow the robust identification of clinically relevant dermatophytes, using a variety of strains, incubation times, and growth conditions. First, we established a quick and reliable method for sample preparation to obtain a reliable and reproducible identification independently of the growth conditions. The Vitek MS V2.0.0 fungal knowledge base was then expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 35 publications
3
49
2
3
Order By: Relevance
“…Previous studies have shown that MALDI-TOF MS is a rapid and accurate method for the identification of dermatophytes. There have been many studies examining this group of molds, with identification rates of Ͼ90% for these studies (12,13,(20)(21)(22). Our study correctly identified 100% (14/14) of the dermatophytes tested.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous studies have shown that MALDI-TOF MS is a rapid and accurate method for the identification of dermatophytes. There have been many studies examining this group of molds, with identification rates of Ͼ90% for these studies (12,13,(20)(21)(22). Our study correctly identified 100% (14/14) of the dermatophytes tested.…”
Section: Discussionmentioning
confidence: 56%
“…Prior studies have evaluated the accuracy of MALDI-TOF MS for the identification of only a few genera or groups of organisms, such as Aspergillus spp. or the dermatophytes (12,13,(19)(20)(21)(22)(23)(24)(25)(26). In our study, which examined 319 isolates from 43 different genera, the Vitek MS version 3.0 library was able to correctly identify 66.8% of isolates and 76.8% of the isolates after additional SARAMIS analysis.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, the expanded database was challenged with 131 clinical isolates of dermatophytes belonging to 13 taxa. For 10 taxa, the rate of correct identifications was 100%, including Trichophyton erinacei (1 isolate) and Trichophyton terrestre (1 isolate); in contrast, only 15 of 19 (78.9%) African Trichophyton rubrum (also called Trichophyton soudanense) isolates were correctly identified (this rate was clearly lower than that for T. rubrum sensu stricto isolates [100%]), with several isolates being misidentified as Trichophyton violaceum, demonstrating the close relationship of these two taxa (31). Later, in another study, the Bruker Biotyper database was supplemented with additional mass spectra from 24 (13 reference [United Kingdom National External Quality Assessment Service {UK NEQAS}] and 11 clinical) morphologically and/or molecularly (i.e., by ITS DNA sequencing) characterized strains of 13 different species (32).…”
Section: Rhizopus-lichtheimia Species Previous Reports On the Maldi-mentioning
confidence: 92%
“…Although these methods can provide accurate results, they are expensive, require specialized equipment or expertise, and are not commonly available in clinical laboratories. In the present review, findings from the 10 studies (23)(24)(25)(27)(28)(29)(30)(31)(32)(33) shown in Table 1 indicate that before MALDI-TOF MS testing, only one study identified isolates via conventional phenotypical analyses (33), whereas almost all the remaining studies also sequenced all their isolates, and in two studies, only molecular biology analyses of the isolates were undertaken (27,28). This supports the idea that the overall high level of accuracy of MALDI-TOF MS-based mold identification shown in these studies might not be overestimated.…”
Section: Mold Identification By Maldi-tof Ms: Is It Really a History mentioning
confidence: 99%
See 1 more Smart Citation